Obtenção de derivados de compostos isolados de Zingiber officinale por biotransformação e semi-síntese e avaliação frente à cisteinil-proteases - Ávila, Roberta Marques Dias de (Universidade Federal de São Carlos, 2016)
Several aromatic polyketide derivatives from Ginger (Zingiber officinale), like zingerone, 6-gingerol and 6-shogaol were obtained by biocatalytic reactions and semi-synthesis and both their antifungal and cysteine-proteinase inhibitory properties were investigated. The derivatives obtained by semi-synthesis were evaluated in the form of a first screening for inhibition property of growth of phytopathogenic fungi Colletotrichum gloesporioides and Fusararium oxysparum. The biotransformation of four compounds: zingerone purchased from Sigma Aldrich, 6-gingerol isolated from ginger and its derivatives 4-methyl-6-gingerol and 6-shogaol was investigated using whole cells of C. gloesporioides and showed recognition of the fungal pool of enzymes capable of using such compounds as substrates. All experiments were conducted in sterile liquid medium BD (Potato and Dextrose) under agitation (120 rpm) and constant temperature (30° C ), obtaining the methanol extract of mycelial mass (MM), the aqueous extract (Aq) and the ethyl acetate extract (Ac) of culture fluid. The ethyl acetate extract was analyzed by GC-MS and ESI-MS/MS using LC-MS techniques. The fungus C. gloesporioides proved able to promote a reaction of aromatic oxidative coupling of zingerone, forming a dimer of this molecule. This product was isolated, identified by NMR spectroscopy and high resolution mass spectrometry. The biotransformation experiment was also made with isotopically labeled zingerone with deuterium. Analysis of the ethyl acetate extract (Ac) by (-) ESI-MS / MS using LC-IT-MS showed that dimer formation since the first day once the isotopically labeled fragments were detected. The aromatic oxidative coupling reaction also occurs in the biotransformation to phenolic compound 6-gingerol by C. gloesporioides. It is probable that side chain of 6-gingerol was used as carbon source forming an alcohol with molecular mass 168 Da. The dimer of the alcohol appears as biotransformation product. Among the proposed semi-synthesis reactions, the insertion of an oxime ether subunit from zingerone as starting material was obtained. Despite the molecular modeling indicates good complementarity with the catalytic site model cysteinyl preoteases, the product obtained does not show inhibitory activity against the enzymes L and V to 25 uM. The oximine derivative of 8-gingerol, presented halo of inhibition against the proliferation of fungus C.gloesporioides in disk diffusion test on PDA (Potato Dextrose Agar) in a Petri dish. The ethyl acetate extract (Ac) from the tenth day showed a good result of inhibition of cathepsin V (80%). There are studies that investigate the relationship between the antifungal activity of compounds of the property of inhibiting cysteine-preoteases as papain and cathepsin B and L.
Bioprospecting of derivatives compounds isolated from ginger (Zingiber officinalle) using biocatalytic reactions and semi-synthesis: cysteine-proteinase inhibition properties
Keywords: Biotransformação; Zingiber officinale; Colletotrichum gloesporioides; Fusarium oxysporum; Semi-síntese; CIENCIAS EXATAS E DA TERRA::QUIMICA